The effects of adhesion on the tensile strength of steel-polymer sandwich composites. (3rd September 2021) - Han, Sungjin; Sung, Minchang; Jang, Jinhyeok; Jeon, Seung-Yeol; Yu, Woong-Ryeol
Abstract : Steel-polymer sandwich composites are relatively strong and lightweight materials. However, accurately predicting the mechanical properties of these materials has been challenging, presumably due to a lack of consideration of their interfacial properties. In this study, the interfacial adhesion in sandwich composites was systematically varied to evaluate its effects on mechanical properties, particularly tensile strength. Next, we investigated why the tensile capacity (strength) of each component is not fully realized for seemingly simple structures consisting of two steel layers and a core polymer layer when assuming relatively weak adhesion. The resulting interfacial properties of the sandwich composites were characterized and incorporated into a cohesive zone model for finite element simulation. The simulation results revealed that, in contrast to the strong adhesion case, weak adhesion leads to stress concentration around failed cohesive elements, resulting in earlier failure of constituent layers and thus a lowering of the overall tensile strength of the composite.